ЭФФЕКТИВНОСТЬ КАЗАХСТАНСКИХ БИОПРЕПАРАТОВ ДЛЯ БОРЬБЫ С НЕПАРНЫМ ШЕЛКОПРЯДОМ (Experimental biology, 2015)
The fight against gypsy moth caterpillars (Lymantria dispar L.) in the field and laboratory evaluated the biological activity of bacterial bioinsecticides created on the basis of the Kazakh strains of Bacillus thuringiensis Berliner. Larvibakt was gained in 2011, National Biotechnology Center (NBC) branch in Stepnogorsk based k-Ym07/KB strain isolated from the larvae of the codling moth, and the active principle is Ak kobelek strain 2127-3k, isolated in 2004 from the American white butterfly caterpillars. Both strains were stored in acollection of entomopathogenic microorganisms laboratory ofbiotechnology LTD "The Kazakh Research Institute for Plant Protection and Quarantine".Due to the set of laboratory experiments were obtained quite good results. With the death of the pest infection load on the fifth day was more than 98%.Conducted in the processing area Enbekshikazakh prototypes based on the biological Bacillus thuringiensisstrains in comparison with the reference lepidotsid in the fight against dangerous quarantine pest caterpillars also showed high efficiency ( 90%) .
Keywords: bacterial bioinsecticides